Microscopic Characteristics of Fractured Sandstone after Cyclic Freezing-Thawing and Triaxial Unloading Tests - Xiaohui Ni; Xiaomei Shen; Zhende Zhu (Advances in Civil Engineering)
The understanding of tunneling rock failure characteristics under unloading conditions in the cold region is critical for the proper design of rock tunneling support and mining safety operation. Given this understanding is currently limited, this study aimed to investigate the characteristics of fractured sandstone samples in the microscale after cyclic freezing-thawing and triaxial unloading tests. The samples were first subjected to different cycles of freezing and thawing, followed by the triaxial unloading test and scanning electron microscopy imaging. The peak strength and damage dilatancy stress were measured from the stress-strain curves. The microcrack characteristics (number, length, and width) were obtained through the image analysis. The results show that the decrease in peak strength and damage dilatancy stress was more significant by the first 20 freezing-thawing cycles when the pore pressure gradient is maximum compared to the later freezing-thawing cycles. The mechanical properties also significantly deteriorated when the severe freezing-thawing treatments were performed. The fracture section mainly had the morphology of honeycomb-like microstructure, stripped microstructure, and flocculent microstructure. The cracking extent was mainly influenced by the freezing-thawing rather than the triaxial unloading test, but the azimuthal angle of microcracks was significantly altered by the triaxial unloading. To properly design rock tunneling support and safe operation of mining in the cold region, both impact of cyclic freezing-thawing and the excavation operation direction should be considered.